Exploring Religious Moderation through Student-Written Flash Fiction - Aflahah Aflahah; Siti Azizah; Eva Nikmatul Rabbianty; Moh. Syafik; Aemy Elyani Mat Zain (Indonesian Language Education and Literature, 2025)
This study examines the integration of religious moderation values through flash fiction written by students. The research design used mixed methods involving 25 students. The data collected consisted of quantitative and qualitative data. Data were collected through a questionnaire related to students' understanding of religious moderation. The results of the initial questionnaire became the basis for teachers in delivering the material to students. After being given the material, students were asked to create a short story containing religious moderation. After completing the story, students were asked to complete a questionnaire containing three questions related to their understanding of religious moderation, its application in the story, and its application in everyday life. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed using thematic analysis. The results showed a strong understanding of religious moderation and creative application of it in narratives. Quantitative findings showed an average increase of 20%. These results indicate that flash fiction is a promising educational tool for promoting religious moderation. The initial survey results showed that most students had experienced incidents of intolerance. Data from student-generated stories indicate that the majority of students understand religious moderation as "accepting and respecting the beliefs of others," practicing tolerance through fictional stories, and applying it in daily life. Religious moderation can be effectively implemented through learning models, such as writing flash fiction. Practically, this study offers a replicable framework for educators to integrate moral education into literacy development. These findings suggest that implementing student-centered activities, such as flash fiction, into the curriculum can foster empathy, tolerance, and social harmony in diverse classroom environments. The results of this study are expected to provide alternatives for teachers when teaching the same or other materials.Menggali Moderasi Beragama melalui Karya Flash Fiction SiswaPenelitian ini mengkaji integrasi nilai-nilai moderasi beragama melalui flash fiction yang ditulis oleh siswa. Desain penelitian menggunakan mixed methods yang melibatkan 25 siswa. Data yang dikumpulkan terdiri dari data kuantitatif dan kualitatif. Data dikumpulkan melalui angket terkait pemahaman siswa tentang moderasi beragama. Hasil angket awal menjadi dasar bagi guru dalam menyampaikan materi kepada siswa. Setelah diberi materi, siswa diminta untuk membuat cerita pendek yang memuat moderasi beragama. Selesai membuat cerita, siswa diminta mengisi angket yang memuat tiga pertanyaan terkait pemahaman moderasi beragma, penerapannya dalam cerita, dan penerapannya dalam kehidupan sehari-hari. Data kuantitatif dianalisis menggunakan statistik deskriptif, sedangkan data kualitatif dianalisis menggunakan analisis tematik. Hasil penelitian menunjukkan pemahaman yang kuat tentang moderasi beragama dan secara kreatif menerapkannya dalam narasi. Temuan kuantitatif menunjukkan peningkatan rerata sebesar 20%. Hasil ini menunjukkan bahwa flash fiction merupakan alat edukatif yang menjanjikan untuk mempromosikan moderasi beragama. Hasil survei awal menunjukkan bahwa Sebagian besar siswa pernah mengalami peristiwa intoleransi. Data dari cerita yang dibuat oleh siswa menunjukkan bahwa mayoritas siswa memahami moderasi beragama sebagai "menerima dan menghormati keyakinan orang lain", menerapkan toleransi melalui cerita fiksi, dan menerapkannya dalam kehidupan sehari-hari. Moderasi beragama dapat diterapkan secara efektif melalui model pembelajaran, seperti penulisan fiksi kilat. Secara praktis, studi ini menawarkan kerangka kerja yang dapat direplikasi bagi para pendidik untuk mengintegrasikan pendidikan moral ke dalam pengembangan literasi. Temuan ini menunjukkan bahwa penerapan kegiatan yang berpusat pada siswa, seperti fiksi kilat, ke dalam kurikulum dapat mendorong empati, toleransi, dan harmoni sosial dalam beragam lingkungan kelas. Hasil penelitian ini diharapkan dapat menjadi alternatif bagi guru ketika mengajar materi yang sama atau materi lain.